A memory of Solferino - Dunant, Henry, 1828-1910.; American National Red Cross. District of Columbia Chapter (Washington, D.C. : American National Red Cross, 1959)
"A translation from the French of the first edition published in 1862. This edition contains also a short biography of Dunant and a section on the origins and growth of the Red Cross movement and the Geneva Conventions in the century following the Battle of Solferino."
Henri Dunant, 1828-1910 -- A memory of Solferino -- The Power of a Great Idea
"A translation from the French of the first edition, published in 1862."
"American edition issued on hundredth anniversary of the Battle of Solferino, 1959."
Keywords: Geneva Convention (1864); Red Cross and Red Crescent; Solferino, Battle of, Solferino, Italy, 1859.; Military hygiene; Medicine, Military; Warfare; Voluntary Health Agencies -- history; Red Cross; Italy; Italy -- Solferino; Personal Narrative